2022
DOI: 10.1038/s41389-022-00396-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-specific enolase promotes stem cell-like characteristics of small-cell lung cancer by downregulating NBL1 and activating the BMP2/Smad/ID1 pathway

Abstract: Little is known about the biological functions of neuron-specific enolase (NSE) as a specific biomarker for small-cell lung cancer (SCLC). Herein, we elucidate the effect and mechanism of NSE on SCLC stem cell-like characteristics. Upregulated NSE expression was observed in spheroid cells. The gain-of-function and loss-of-function approaches demonstrated that modulation of NSE positively regulated cell proliferation, drug resistance, spherical clone formation, tumor growth, and stem cell-like characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…GO and KEGG enrichment analyses linked differential gene expression in stalk‐like cells to the functions of endothelial cells (such as fluid shear stress and regulation of angiogenesis) as well as initiation and development of tumors such as SCLC (Figure 3D‐F). For example, the differentially expressed gene ID1 has been shown to enhance angiogenesis and stem cell‐like characteristics of SCLC 23 . Vascular endothelium is exposed to fluid shear stress from blood flow, and such stress mediates the remodeling of existing blood vessels and development of new ones, which in turn influences risk of cancer metastasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GO and KEGG enrichment analyses linked differential gene expression in stalk‐like cells to the functions of endothelial cells (such as fluid shear stress and regulation of angiogenesis) as well as initiation and development of tumors such as SCLC (Figure 3D‐F). For example, the differentially expressed gene ID1 has been shown to enhance angiogenesis and stem cell‐like characteristics of SCLC 23 . Vascular endothelium is exposed to fluid shear stress from blood flow, and such stress mediates the remodeling of existing blood vessels and development of new ones, which in turn influences risk of cancer metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the differentially expressed gene ID1 has been shown to enhance angiogenesis and stem cell-like characteristics of SCLC. 23 Vascular endothelium is exposed to fluid shear stress from blood flow, and such stress mediates the remodeling of existing blood vessels and development of new ones, which in turn influences risk of cancer metastasis. Silencing of CAV1, which was linked to fluid shear stress in our study, increases sensitivity of nonsmall cell lung cancer to cisplatin-induced apoptosis.…”
Section: Chemotherapy Promotes Angiogenesis By Endothelial Cells In T...mentioning
confidence: 99%
“…However, a sub-analysis reported that it was not a prognostic factor in the group that underwent chemotherapy or surgery plus chemotherapy [20]. NSEs have been reported to promote cancer stem cell-like properties for small cell lung cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, a sub-analysis reported that NSE was not a prognostic factor in the group that underwent chemotherapy or surgery plus chemotherapy (Tian et al 2020 ). NSEs have been reported to promote cancer stem cell-like properties in small cell lung cancer (Lu et al 2022 ). These results suggest that NSE is a prognostic factor in the limited stage (Lu et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%